Study of Physical Characteristic, Water Vapor Transmission Rate and Inhibition Zones of Edible Films from Aloe vera (Aloe barbadensis) Incorporated with Yellow Sweet Potato Starch and Glycerol - Nur Rahmiatiningrum; Sukardi Sukardi; Warkoyo Warkoyo (Universitas Muhammadiyah Malang, 2019)
Glucomannan was the main polysaccharide of Aloe vera gel. It was dissolved in water, formed a gel, and transparent as a film. Aloe vera gel was reported antimicrobial and antioxidant activity such as saponin and anthraquinone that was potential for the increased value of an edible film. However, Aloe vera gel form weak film caused glucomannan to have high water absorption. In this research, Aloe vera gel was used as a basis for the polymer film. Yellow sweet potato starch added for the strength matrix component used amylose. This starch expected to give colors from carotenoids. Glycerol also added for the flexibility of an edible film. Randomized Complete Block Design Factorial (RCBD) was applied. The first factor was concentration of yellow sweet potato starch (1%, 2%, 3%) and the second one was glycerol (0,1%, 0,25%, and 0,5%). The parameters tested were color, thickness, transparency, tensile strength, elongation, solubility, water vapor transmission rate, and inhibition zones against E. coli, and S. aureus, fungi A. niger and C. Albicans. The results showed that the addition of yellow sweet potato starch and glycerol with different concentration had a significant effect on color, thickness, transparency, tensile strength, elongation, and solubility. However, an edible film on this research has not to show bacteria and fungi inhibition zone of edible film. P2G1 is the best treatment (yellow sweet potato starch 2% and glycerol 0,1%) produced an edible film with a thickness of 0.12mm, elongation 50.85%, tensile strength 0.55 MPa, solubility 41.03%, transparency 2.13%, vapor transmission rate 3,40 g/m2/24hours, L, a+, b+ score in sequence 41.87, 0.2, and 4.1.